1996
DOI: 10.1210/jcem.81.2.8636292
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in type I diabetes mellitus: a major role for reduced glucose extraction.

Abstract: We determined whether insulin resistance in Type I diabetes is caused by a defect in glucose extraction or blood flow and whether it is the rate of glucose metabolism rather than insulin that increases blood flow in these patients. To make this determination, 9 Type I diabetic patients (age 33 +/- 3 yr, body mass index 24 +/- 1 kg/m2, HbA1c 8.3 +/- 0.1%) and 10 matched normal subjects were first studied under normoglycemic hyperinsulinemic conditions. The diabetic patients were then restudied under similar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In skeletal muscle in the two studies available insulin induced vasodilation was reduced in one study [48] but was normal in another study [49] in Type I diabetic patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In skeletal muscle in the two studies available insulin induced vasodilation was reduced in one study [48] but was normal in another study [49] in Type I diabetic patients.…”
Section: Discussionmentioning
confidence: 94%
“…2 days) is not feasible in non-diabetic subjects. In peripheral vasculature the effects of acute hyperglycaemia on blood flow are controversial because in one study hyperglycaemia blunted insulin induced vasodilation [48] while in another more recent study hyperglycaemia did not alter blood flow or its response to insulin [49].…”
Section: Discussionmentioning
confidence: 99%
“…The latter studies have been performed under intravenously maintained normoglycemic hyperinsulinemic (clamp) conditions, where the insulin concentrations have been either in the high physiological (2,4,5) or supraphysiological (6) range. Under physiological hyperglycemic hyperinsulinemic conditions after an oral glucose load or a meal (7,8), as well as in the basal state (7,9), the absolute rates of glucose uptake (7)(8)(9) and blood flow are normal (9,10), possibly because hyperglycemia compensates for defects in blood flow (11,12) or glucose extraction (13,14). The reason for the discrepant results regarding insulin stimulation of blood flow is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…
Type I (insulin-dependent) diabetes mellitus is characterised by pronounced insulin resistance for glucose disposal in skeletal muscle [1,2]. This metabolic impairment is at least in part related to a post-insulin signalling defect in the expression and translocation of GLUT4 glucose transporters to the muscle cell surface [3±5].
…”
mentioning
confidence: 99%
“…This metabolic impairment is at least in part related to a post-insulin signalling defect in the expression and translocation of GLUT4 glucose transporters to the muscle cell surface [3±5]. The lack of insulin action on glucose metabolism in muscle of people with Type I diabetes could also be explained by an impaired vasodilatory effect of insulin on the muscle vasculature [2], although this impairment has not been confirmed in a more recent study [1]. Several studies have shown that endothelium-dependent relaxation is altered in Abstract Aims/hypothesis.…”
mentioning
confidence: 99%